The Impact of Formal Entrepreneurship and Economic Freedom on the Size of the Shadow Economy in Asian Countries - Dang, Buu Kiem (Organizations and Markets in Emerging Economies, 2025)
This study aims to evaluate the impact of formal entrepreneurship and economic freedom on the size of the shadow economy in Asian countries. The research sample includes 22 Asian countries over the period from 1995 to 2018. The study employs reliable panel data estimation methods, including the Fixed Effects Model with robust standard errors method, the Driscoll-Kraay standard errors method, and the two-step system GMM method. The findings indicate that formal entrepreneurship has a positive relationship with the size of the shadow economy, while economic freedom and its two sub-components, business freedom and trade freedom, reduce the size of the shadow economy. Additionally, economic freedom, business freedom, and trade freedom play a moderating role in reducing the positive relationship between formal entrepreneurship and the size of the shadow economy. Our study suggests that governments should comprehensively evaluate the effectiveness of policies promoting entrepreneurship and consider expanding economic freedom, particularly business freedom and trade freedom.